Preparation method of low-impurity and high-compaction iron phosphate

Through multi-step treatment, including dilute sulfuric acid heating, ammonia water and aluminum remover filtration, phosphate and sulfate adjustment, the content of aluminum and titanium impurities in iron phosphate was successfully reduced, the purity and stability of iron phosphate was improved, and the existing solution was solved. The impurity removal problem in the technology has achieved the preparation of low-hetero-high-pressure iron phosphate.

CN119240636APending Publication Date: 2025-01-03HUNAN YACHENG NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411383614.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing phosphate ferric slag leaching liquid has high impurities, especially aluminum and titanium, which makes it difficult to remove, resulting in difficult to ensure the purity and consistency of iron phosphate and affecting the performance of lithium batteries.

Method used

Filter with mixed heat of dilute sulfuric acid, phosphorus iron slag and iron powder, followed by adding ammonia water and aluminum remover for filtering, then adding phosphate and sulfate, finally adding oxidant and calcining treatment, removing impurities through multiple steps and controlling the proportion of main components , prepare low-hetero-high compacted iron phosphate.

Benefits of technology

It significantly reduces the content of aluminum and titanium impurities, improves the purity and performance stability of iron phosphate, ensures the control of the particle size, sulfur content and Fe/P ratio of the product, enhances the stability and repeatability of the process, and meets high pressure Real product requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070499010000221
    Figure BDA0005070499010000221
  • Figure HDA0005070499030000011
    Figure HDA0005070499030000011
Patent Text Reader

Abstract

The invention discloses a preparation method of low-impurity and high-compaction iron phosphate. The preparation method of the iron phosphate comprises the following steps: S1, mixing dilute sulphuric acid, ferrophosphorus slag and iron powder, heating and filtering to obtain carbon slag, a mixed solid and a leachate 1; s2, adding ammonia water into the leachate 1, and filtering to obtain leachate 2; s3, adding an aluminum removal agent into the leachate 2, and filtering to obtain leachate 3; s4, adding phosphate and sulfate into the leachate 3 to obtain a reaction solution; s5, adding an oxidizing agent and water into the reaction solution to obtain reaction slurry; and S6, pouring the reaction slurry into a reaction kettle, and carrying out heating reaction, aging, washing and calcining treatment to obtain the iron phosphate. According to the method, the content of impurities in iron phosphate is effectively reduced, the product quality and the process stability are improved by optimizing a reaction system, and the method plays an important role in promoting the development of related industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrophosphorus slag recovery, in particular to a method for preparing low-impurity and high-density ferric phosphate. Background Art

[0002] As an important chemical raw material, ferric phosphate is widely used in the fields of lithium battery positive electrode materials. In recent years, with the rapid development of the lithium battery industry, the demand for ferric phosphate has increased significantly, and the preparation technology has been continuously optimized. However, there are still many problems in the process of preparing ferric phosphate using ferrophosphorus slag leaching solution, especially the high impurity content of the finished product and the poor consistency of various indicators, which seriously restricts the improvement of its product quality. The root of these problems lies in the complex composition of ferrophosphorus slag, especially the high content of impurities such as aluminum and titanium, and the large fluctuations in the content of main elements such as iron, phosphorus, and sulfur, which brings great challenges to the control of the reaction process.

[0003] First of all, ferrophosphorus slag, as a solid waste generated in the lithium extraction process, has complex components and large batch differences. The valuable elements in these slags, such as iron and phosphorus, can be recycled through acid leaching, but at the same time, the slag contains a large amount of impurities, especially aluminum, titanium and other elements. These impurities often have similar chemical properties to the main component of iron phosphate, so it is difficult to completely separate them during the leaching process. Although the existing acid leaching process can partially remove impurities, the effect is not ideal, especially when dealing with aluminum and titanium, because these elements have complex chemical properties in the solution and usually exist in multiple forms, which increases the difficulty of impurity removal. For example, aluminum can be extracted in the form of Al 3+ It exists in the form of in acidic solution, and can also form colloids or precipitation under certain conditions, which makes the removal process of aluminum more complicated. Titanium often exists in the form of TiO2, which has relatively stable chemical properties and is difficult to remove through conventional chemical reactions.

[0004] Secondly, due to the diversity of their sources, the impurity content of different batches of ferrophosphorus slag fluctuates greatly. The composition of ferrophosphorus slag is affected by many factors, including the source of the ore, the conditions of the lithium extraction process, the type of reaction medium, etc. Therefore, although valuable elements such as iron and phosphorus can be extracted from ferrophosphorus slag by acid leaching, there are significant differences in the content of these elements in each batch of leachate. For example, some batches of ferrophosphorus slag have a higher iron content, while other batches may be dominated by phosphorus content. This instability of elemental composition places higher demands on the subsequent iron phosphate synthesis process. To ensure the quality and consistency of the final product, the leachate of different batches must be carefully analyzed and adjusted, but in actual industrial production, real-time monitoring and adjustment are often difficult to achieve, which leads to fluctuations in product quality.

[0005] Third, the ferrophosphorus slag leaching solution contains not only target elements such as iron and phosphorus, but also sulfur. Sulfur exists in various forms during the lithium extraction process, including sulfate ions (SO4 2- ) and sulfite ions (SO3 2- ) and so on. These sulfides may react with iron, phosphorus and other elements in the subsequent reaction process to form unstable intermediates, which in turn affect the purity and performance of iron phosphate. For example, under high temperature conditions, sulfate ions may react with iron to form ferric sulfate, which not only affects the efficiency of iron phosphate production, but also introduces new impurities. In addition, the presence of sulfur may also lead to incompleteness of the crystal structure of iron phosphate, affecting its electrochemical performance in applications such as lithium batteries.

[0006] In addition to the impurity problem, the fluctuation of the content of the main components such as iron, phosphorus, and sulfur in the ferrophosphorus slag leachate is also one of the key factors leading to unstable product quality. In the preparation process of iron phosphate, the molar ratio of iron to phosphorus is an important parameter that determines the performance of the final product. If the ratio of iron to phosphorus is not properly controlled, it may cause abnormalities in the crystal structure of iron phosphate, which in turn affects its electrochemical properties. For example, excessive iron content may cause excessive iron elements in the crystal to enter the structural defect position, producing excessive iron oxides, which will have an adverse effect on the performance of the battery during the use of lithium batteries. Similarly, if the phosphorus content is insufficient, a complete iron phosphate crystal structure may not be formed, resulting in a decrease in the electrochemical activity of the product. Therefore, during the preparation process, the ratio of iron to phosphorus must be strictly controlled to ensure that the structure and performance of the product meet the expected standards.

[0007] In addition to the ratio of iron and phosphorus, fluctuations in sulfur content will also affect product performance. Although the impact of sulfur on the product can be reduced through proper regulation in some processes, in most cases, the presence of sulfur is still a problem that cannot be ignored. Excess sulfur may lead to a decrease in the electrochemical stability of iron phosphate, and will also affect its cycle life and charge and discharge efficiency in the battery. In order to reduce the impact of sulfur, additional processing steps are usually required during the preparation process, such as adding specific reactants or adjusting reaction conditions, but these processing steps often increase production costs and reduce the economic efficiency of the process.

[0008] As a positive electrode material for lithium batteries, iron phosphate has extremely strict performance requirements. The high impurity content and composition fluctuation problems in the prior art make it difficult to ensure the consistency of the product, which directly affects the performance of iron phosphate in lithium battery applications. The requirements of lithium batteries for positive electrode materials include high energy density, long cycle life, and excellent safety and stability. However, iron phosphate with high impurity content often performs poorly in these properties. For example, the presence of impurities may cause the conductivity of the positive electrode material to decrease, affecting the transmission efficiency of lithium ions, thereby reducing the capacity and energy density of the battery. In addition, impurities may gradually accumulate during the charge and discharge cycle to form local electrochemical reaction centers, resulting in a shortened cycle life of the battery and even causing safety hazards.

[0009] In addition, the fluctuation of the composition of different batches of iron phosphate products will also affect the consistency of lithium batteries. In large-scale production, the consistency of batteries is crucial to the performance and safety of the entire vehicle. If there are significant differences in the composition of each batch of iron phosphate materials, it may cause the battery pack to exhibit different charging and discharging characteristics during use, thereby affecting the vehicle's range and safety performance. Therefore, how to reduce the adverse effects of composition fluctuations in the preparation process of iron phosphate is an urgent problem to be solved in the current iron phosphate production process. Summary of the invention

[0010] The purpose of the present invention is to prepare a low-impurity and high-density ferric phosphate.

[0011] The first aspect of the present invention is:

[0012] Provided is a method for preparing iron phosphate.

[0013] The second aspect of the present invention is:

[0014] Application of the preparation method of ferric phosphate.

[0015] Specifically, the technical solution adopted according to the first aspect of the present invention is:

[0016] A method for preparing ferric phosphate comprises the following steps:

[0017] S1 is mixed with dilute sulfuric acid, ferrophosphorus slag and iron powder, and heated and filtered to obtain carbon slag, mixed solid and leachate 1;

[0018] S2 adding ammonia water to the leachate 1, filtering to obtain leachate 2;

[0019] S3: adding an aluminum removal agent to the leachate 2, and filtering to obtain a leachate 3;

[0020] S4 adds phosphate and sulfate to the leaching solution 3 to obtain a reaction solution;

[0021] S5 adding an oxidant and water to the reaction solution to obtain a reaction slurry;

[0022] S6: pouring the reaction slurry into a reaction kettle, and obtaining the iron phosphate after temperature-raising reaction, aging, washing and calcination.

[0023] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0024] The present invention effectively reduces the aluminum and titanium impurity contents in the ferrophosphorus slag leachate, wherein the aluminum impurity is reduced from 427ppm to 36ppm, and the titanium impurity is reduced from 250ppm to 28ppm. This improvement significantly improves the purity of ferrophosphate and enhances its performance stability in subsequent applications.

[0025] By targeting the fluctuation of the main component ratio of different batches of leachate, the present invention successfully achieves precise control of the main component ratio by adding phosphate and sulfate. This measure ensures that the product particle size D50 is stable at 4-6μm, the sulfur content is controlled at 30-50ppm, and the BET specific surface area reaches 8.5-11.5m 2 / g, the Fe / P ratio is maintained at 0.968-0.971, and the impurity contents of aluminum and titanium are controlled within <100ppm, which greatly improves the stability and repeatability of the entire process.

[0026] The compacted density of the iron phosphate powder prepared by the present invention can reach 2.45g / cm 3 The above meets the requirements of high-density products. This feature makes iron phosphate more widely used in energy storage, batteries and other fields, and can improve the overall performance of the final product.

[0027] In summary, the present invention not only effectively reduces the content of impurities in ferric phosphate, but also improves the quality of the product and the process stability by optimizing the reaction system, which plays an important role in promoting the development of related industries.

[0028] According to one embodiment of the present invention, the molar ratio of the dilute sulfuric acid to the iron in the ferrophosphorus slag is 1.6-1.8:1-1.2.

[0029] According to one embodiment of the present invention, the concentration of the dilute sulfuric acid is 6-7 mol / L.

[0030] According to one embodiment of the present invention, the molar ratio of the iron powder to the iron in the ferrophosphorus slag is 0.6-0.8:1-1.2.

[0031] According to one embodiment of the present invention, the step S1 further includes the following steps: firstly mixing dilute sulfuric acid and ferrophosphorus slag, and then adding iron powder after heating.

[0032] According to one embodiment of the present invention, in step S1, the temperature is increased to 95-98°C.

[0033] According to one embodiment of the present invention, in step S1, the iron powder is evenly added within 4 hours.

[0034] According to one embodiment of the present invention, in the step S1, after the iron powder is added, filtering operation is performed after 5-6 hours.

[0035] According to one embodiment of the present invention, in step S2, after adding ammonia water to the leachate 1, the pH value of the solution is adjusted to 1.6-2.4. By adding ammonia water and adjusting the pH to a specific range, the titanium impurities in the leachate 1 are converted into Ti(OH)4 precipitates, thereby removing the titanium impurities.

[0036] According to one embodiment of the present invention, in step S3, an aluminum removal agent is added to the leachate 2, and the leachate is allowed to stand for 4 hours at room temperature for reaction, and then filtered. The present invention adds an aluminum removal agent to the leachate 2, the main purpose of which is to complex the aluminum impurities in the leachate 2 into Na3AlF6 precipitates to remove the aluminum impurities.

[0037] According to one embodiment of the present invention, in step S3, the molar ratio of the aluminum removal agent to the aluminum ions in the leaching solution 2 is 8.4-8.6:1-1.2.

[0038] According to one embodiment of the present invention, in step S4, after adding the phosphate and sulfate to the leachate 3, the molar ratio of iron, phosphorus and sulfur in the leachate 3 is 1:1.15-1.40:0.7-1.0. The main purpose is to adjust the ratio of the main components of the reaction slurry to obtain iron phosphate with specific physical and chemical indicators.

[0039] According to one embodiment of the present invention, in step S4, the phosphate includes at least one of monoammonium phosphate, diammonium phosphate, calcium phosphate and potassium phosphate.

[0040] According to one embodiment of the present invention, in step S4, the sulfate includes at least one of ammonium sulfate, sodium sulfate, calcium sulfate, magnesium sulfate and copper sulfate.

[0041] According to one embodiment of the present invention, in step S5, the oxidant comprises hydrogen peroxide. In the present invention, hydrogen peroxide is added to the reaction solution to remove Fe 2+ Oxidized to Fe 3+ After testing for the absence of ferrous ions, adjust the Fe 3+ Reaction concentration.

[0042] According to one embodiment of the present invention, in step S5, the Fe 3+ The concentration is 0.6-1.0 mol / L. When Fe 3+ The concentration is adjusted to 0.6-1.0 mol / L, and amorphous iron phosphate precipitate will be generated.

[0043] According to one embodiment of the present invention, in step S6, the calcination temperature is 550-600°C.

[0044] According to one embodiment of the present invention, in step S6, the temperature of the temperature-raising reaction is 93-95°C.

[0045] According to one embodiment of the present invention, in step S6, the aging time is 2.5-3 hours. Ferric phosphate dihydrate is prepared in the slurry through temperature-raising reaction and aging treatment.

[0046] According to one embodiment of the present invention, in step S6, the washing needs to wash the slurry until the water conductivity is <500uS / cm, so as to clean the dihydrate iron phosphate in the slurry, and then calcination is performed to remove crystal water to obtain anhydrous iron phosphate.

[0047] Specifically, the technical solution adopted according to the second aspect of the present invention is:

[0048] Another aspect of the present invention further provides a positive electrode material for a lithium battery, including the iron phosphate prepared by the method of the first embodiment. Since the application adopts all the technical solutions of the above-mentioned method for preparing iron phosphate, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment.

[0049] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0051] Figure 1 The following is a flow chart of the preparation method of Examples 1-7. DETAILED DESCRIPTION

[0052] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0053] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0054] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0055] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0056] Example 1

[0057] A method for preparing ferric phosphate comprises the following steps:

[0058] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0059] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.6, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0060] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3; the content of ferrous iron, phosphorus, and sulfur components thereof is tested by ICP, and the ratio is calculated to be 1:0.61:0.83;

[0061] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0062] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.7 mol / L, and a reaction slurry was obtained;

[0063] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0064] Example 2

[0065] A method for preparing ferric phosphate comprises the following steps:

[0066] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature rises to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is added evenly within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0067] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4. After reacting for 1 hour, the solid is removed by filtration to obtain the titanium removal leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0068] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3. The contents of ferrous iron, phosphorus, and sulfur components are tested by ICP, and the ratio is calculated to be 1:0.62:0.79;

[0069] S4 adds monoammonium phosphate and ammonium sulfate to the leachate 3, adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0070] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0071] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0072] Example 3

[0073] A method for preparing ferric phosphate comprises the following steps:

[0074] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0075] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.9, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0076] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.55:0.65;

[0077] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0078] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 1.0 mol / L, and a reaction slurry was obtained;

[0079] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0080] Example 4

[0081] A method for preparing ferric phosphate comprises the following steps:

[0082] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0083] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0084] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0085] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.15:0.84, and obtains a reaction solution after complete dissolution;

[0086] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0087] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0088] Example 5

[0089] A method for preparing ferric phosphate comprises the following steps:

[0090] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0091] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0092] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0093] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.40:0.84, and obtains a reaction solution after complete dissolution;

[0094] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0095] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0096] Example 6

[0097] A method for preparing ferric phosphate comprises the following steps:

[0098] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature rises to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is added evenly within 4 hours. After 5 hours of dissolution and leaching, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0099] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4. After reacting for 1 hour, the solid is removed by filtration to obtain the titanium removal leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0100] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0101] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.7, and obtains a reaction solution after complete dissolution;

[0102] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0103] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0104] Example 7

[0105] A method for preparing ferric phosphate comprises the following steps:

[0106] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature rises to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is added evenly within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0107] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and after reacting for 1 hour, the solid is removed by filtration to obtain the titanium removal leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0108] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0109] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:1.0, and obtains a reaction solution after complete dissolution;

[0110] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0111] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0112] Comparative Example 1

[0113] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, ammonia water is added in step S2 to adjust the pH value of the solution to 1.4.

[0114] Specific:

[0115] A method for preparing ferric phosphate comprises the following steps:

[0116] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0117] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.4, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0118] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3; the content of ferrous iron, phosphorus, and sulfur components thereof is tested by ICP, and the ratio is calculated to be 1:0.61:0.83;

[0119] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0120] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.7 mol / L, and a reaction slurry was obtained;

[0121] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0122] Comparative Example 2

[0123] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, ammonia water is added in step S2 to adjust the pH value of the solution to 2.6.

[0124] Specific:

[0125] A method for preparing ferric phosphate comprises the following steps:

[0126] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0127] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.6, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0128] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3; the content of ferrous iron, phosphorus, and sulfur components thereof is tested by ICP, and the ratio is calculated to be 1:0.61:0.83;

[0129] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0130] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.7 mol / L, and a reaction slurry was obtained;

[0131] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0132] Comparative Example 3

[0133] The difference between Comparative Example 3 and Example 4 is that in Comparative Example 3, in step S4, the ratio of iron, phosphorus and sulfur in the reaction system is adjusted to 1:1.1:0.84.

[0134] Specific:

[0135] A method for preparing ferric phosphate comprises the following steps:

[0136] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0137] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0138] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0139] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.1:0.84, and obtains a reaction solution after complete dissolution;

[0140] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0141] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0142] Comparative Example 4

[0143] The difference between Comparative Example 4 and Example 5 is that in Comparative Example 4, in step S4, the ratio of iron, phosphorus and sulfur in the reaction system is adjusted to 1:1.45:0.84.

[0144] Specific:

[0145] A method for preparing ferric phosphate comprises the following steps:

[0146] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0147] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0148] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0149] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.45:0.84, and obtains a reaction solution after complete dissolution;

[0150] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0151] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0152] Comparative Example 5

[0153] The difference between Comparative Example 5 and Example 6 is that in Comparative Example 5, in step S4, the ratio of iron, phosphorus and sulfur in the reaction system is adjusted to 1:1.37:0.6.

[0154] Specific:

[0155] A method for preparing ferric phosphate comprises the following steps:

[0156] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature rises to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is added evenly within 4 hours. After 5 hours of dissolution and leaching, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0157] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4. After reacting for 1 hour, the solid is removed by filtration to obtain the titanium removal leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0158] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0159] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.6, and obtains a reaction solution after complete dissolution;

[0160] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0161] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0162] Comparative Example 6

[0163] The difference between Comparative Example 6 and Example 7 is that in Comparative Example 6, in step S4, the ratio of iron, phosphorus and sulfur is adjusted to 1:1.37:1.1.

[0164] Specific:

[0165] A method for preparing ferric phosphate comprises the following steps:

[0166] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature rises to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is added evenly within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0167] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 2.4, and after reacting for 1 hour, the solid is removed by filtration to obtain the titanium removal leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0168] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.62:0.79;

[0169] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:1.1, and obtains a reaction solution after complete dissolution;

[0170] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.6 mol / L, and a reaction slurry was obtained;

[0171] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0172] Comparative Example 7

[0173] The difference between Comparative Example 7 and Example 1 is that in Comparative Example 7, the Fe 3+ The reaction concentration was 0.5 mol / L.

[0174] Specific:

[0175] A method for preparing ferric phosphate comprises the following steps:

[0176] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0177] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.6, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0178] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3; the content of ferrous iron, phosphorus, and sulfur components thereof is tested by ICP, and the ratio is calculated to be 1:0.61:0.83;

[0179] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0180] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.5 mol / L, and a reaction slurry was obtained;

[0181] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0182] Comparative Example 8

[0183] The difference between Comparative Example 8 and Example 3 is that in Comparative Example 8, in step S5, Fe 3+ The reaction concentration was 1.1 mol / L.

[0184] Specific:

[0185] A method for preparing ferric phosphate comprises the following steps:

[0186] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours. After dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0187] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.9, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2. The content of aluminum impurities in the solution is tested by ICP sampling;

[0188] S3: adding an aluminum removal agent to the leachate 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 8.4:1; standing the reaction at room temperature for 4 hours, filtering and removing the solid to obtain a defluorinated leachate 3; using ICP to test the contents of ferrous iron, phosphorus, and sulfur, the ratio of which is calculated to be 1:0.55:0.65;

[0189] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0190] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 1.1 mol / L, and a reaction slurry was obtained;

[0191] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0192] Comparative Example 9

[0193] The difference between Comparative Example 9 and Example 1 is that in Comparative Example 9, in step S3, the molar ratio of the aluminum removal agent to the aluminum ions in the leaching solution 2 is 7.8:1.

[0194] Specific:

[0195] A method for preparing ferric phosphate comprises the following steps:

[0196] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0197] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.6, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0198] S3 adds an aluminum removal agent to the leachate 2, and the molar ratio of the aluminum removal agent to the aluminum ion in the leachate 2 is 7.8:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is removed by filtration to obtain a defluorinated leachate 3; the content of ferrous iron, phosphorus, and sulfur components thereof is tested by ICP, and the ratio is calculated to be 1:0.61:0.83;

[0199] S4. Adding monoammonium phosphate and ammonium sulfate to the leachate 3 adjusts the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtains a reaction solution after complete dissolution;

[0200] S5. Add 0.7% hydrogen peroxide to the reaction solution. After testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.7 mol / L, and a reaction slurry was obtained;

[0201] S6: pour the reaction slurry into the reactor and heat it to 93°C. After the slurry turns white and crystallizes, it is aged for 2 hours. After the reaction product is washed until the conductivity of the washing water is <500uS / cm, it is calcined in a muffle furnace at a calcination temperature of 580°C for 4 hours to obtain the iron phosphate.

[0202] Comparative Example 10

[0203] The difference between Comparative Example 10 and Example 1 is that in Comparative Example 10, after completing steps S1-S2, the order of implementing the steps is changed, and hydrogen peroxide is added for treatment first, and then the aluminum removal agent is added for treatment.

[0204] Specific:

[0205] A method for preparing ferric phosphate comprises the following steps:

[0206] S1: Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reaction kettle, mix and heat, the molar ratio of dilute sulfuric acid to iron in ferrophosphorus slag is 1.6:1; when the temperature is raised to 95°C, slowly add iron powder, the molar ratio of iron powder to iron in ferrophosphorus slag is 0.6:1, and the iron powder is evenly added within 4 hours; after dissolving and leaching for 5 hours, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions;

[0207] S2 After the leachate 1 is cooled to room temperature, ammonia water is added thereto to adjust the pH value of the solution to 1.6, and the solid is removed by filtration after reacting for 1 hour to obtain a titanium-removing leachate 2, and a sample is taken for ICP testing of the content of aluminum impurities in the solution;

[0208] S3: adding 0.7% hydrogen peroxide to the reaction solution to obtain an amorphous iron phosphate slurry containing aluminum impurities;

[0209] S4 adds aluminum removal agent to the amorphous iron phosphate slurry, and the molar ratio of the added amount to the aluminum ion in the leachate 2 is maintained at 8.4:1; the reaction is allowed to stand at room temperature for 4 hours, and the solid is filtered out to obtain the defluorinated leachate 3; the content of iron, phosphorus and sulfur components is tested by ICP. At this time, the iron and phosphorus contents are both less than 2g / L, and the iron and phosphorus cannot be leached.

[0210] Comparative Example 11

[0211] The difference between Comparative Example 11 and Example 1 is that in Comparative Example 11, after completing step S1, monoammonium phosphate and ammonium sulfate are directly added to adjust the ratio of iron, phosphorus and sulfur in the reaction system to change the order of implementing the steps.

[0212] Specific:

[0213] A method for preparing ferric phosphate comprises the following steps:

[0214] S1 Pour 6 mol / L dilute sulfuric acid and ferrophosphorus slag into a reactor, mix and heat, and maintain the molar ratio of the amount of dilute sulfuric acid added to the amount of iron in the ferrophosphorus slag at 1.6:1; when the temperature rises to 95°C, slowly add iron powder, and maintain the molar ratio of the amount of iron powder added to the amount of iron in the ferrophosphorus slag at 0.6:1, and add the iron powder evenly within 4 hours. After 5 hours of dissolution and leaching, filter and separate the slurry to obtain a mixed solid of carbon slag and undissolved ferrophosphorus slag and a leachate 1 containing ferrous iron, phosphorus, sulfur and impurity ions; use ICP to test the content of ferrous iron, phosphorus and sulfur components, and the calculated ratio is 1:0.61:0.83;

[0215] S2: adding monoammonium phosphate and ammonium sulfate to the leachate 1 to adjust the ratio of iron, phosphorus and sulfur in the reaction system to 1:1.37:0.84, and obtaining a reaction solution 1 after complete dissolution;

[0216] S3. Ammonia water is added to the reaction solution 1 to adjust the pH value of the solution to 1.6. After reacting for 1 hour, solids are removed by filtration to obtain a titanium removal reaction solution 2. Samples are taken to test the content of aluminum impurities in the solution by ICP.

[0217] S4: adding an aluminum removal agent to the reaction solution 2, wherein the molar ratio of the aluminum removal agent to the aluminum ion in the reaction solution 2 is 8.4:1; allowing the reaction to stand at room temperature for 4 hours, filtering and removing the solid to obtain a reaction solution 3 after defluorination; using ICP to test the contents of ferrous iron, phosphorus, and sulfur components, and the ratio is calculated to be 1:1.41:0.69;

[0218] S5 Add 0.7% hydrogen peroxide to the reaction solution 3, and after testing for the absence of ferrous ions, add pure water to adjust the Fe 3+ The reaction concentration was 0.7 mol / L, and a reaction slurry was obtained;

[0219] S6: Pour the reaction slurry into the reactor and heat it to 93°C. The slurry cannot turn into white crystals.

[0220] Performance Test:

[0221] Take the iron phosphate obtained in Examples 1-7 and Comparative Examples 1-9, and prepare lithium iron phosphate under the same conditions. The preparation method of lithium iron phosphate is as follows: 1. Add lithium carbonate, composite carbon source and water to the prepared iron phosphate, and stir and sand grind it. 2. Spray dry the mixture after sand grinding, and then place the dried material in a protective atmosphere and calcine it at 760°C for 9.5h to obtain lithium iron phosphate. Load the lithium iron phosphate black powder into the compaction density meter mold, and test the powder compaction density with a pressure of 3T. The test results of the embodiments and the comparative examples are shown in Table 1 below.

[0222] Table 1

[0223]

[0224] As can be seen from Table 1 above, the iron phosphate prepared by the scheme of the invention (Examples 1 to 7) can be stably obtained by adjusting the pH of the leachate, the ratio of the main components and the reaction concentration under the condition that the ratio of the main components of the leachate fluctuates, and the particle size D50 is 3.97-5.60 μm, the S content is 30-50.1 ppm, and the BET is 8.61-11.49 m 2 / g, Fe / P 0.968-0.971, Al / Ti content <100ppm, which greatly improves the stability of the entire process; after the electrical performance evaluation of the lithium iron phosphate produced, the powder compaction density can reach 2.462g / cm 3 The above can meet the requirements of high compaction products.

[0225] Compared with Example 1, the pH of the leachate 1 in step S2 of Comparative Example 1 was adjusted to 1.4. Combined with the physical and chemical indicators of the finished product, it can be seen that the S content and Fe / P have changed significantly, and the impurity Ti content exceeds the specification, indicating that the pH of the leachate 1 adjusted in the second step has a minimum value, that is, pH is 1.6.

[0226] Compared with Example 1, the pH of the leaching solution 1 in step 2 of Comparative Example 2 was adjusted to 2.6. Combined with the physical and chemical indicators of the finished product, it can be seen that although the impurity Ti content meets the requirements, the S content and Fe / P are both out of specification, and the electrical performance evaluation shows that the powder compaction density is lower than 2.45 g / cm 3 The above two points indicate that there is an appropriate range for adjusting the pH of the leaching solution 1 in the second step, that is, the pH is between 1.6 and 2.4.

[0227] Compared with Examples 4-5, the main component ratios of the reaction solution in step S4 of Comparative Examples 3-4 were adjusted to 1:1.1:0.84 and 1:1.45:0.84, respectively. Combined with the physical and chemical indicators of the finished product, it can be seen that the S content and Fe / P have changed significantly, and the electrical performance evaluation shows that the powder compaction density is lower than 2.45 g / cm 3 , indicating that there is an appropriate range for adjusting the ratio of phosphate in the reaction solution in the fourth step, that is, the ratio of phosphate to iron ion is between 1.15 and 1.4.

[0228] Compared with Examples 6-7, the main component ratios of the reaction solution in step S4 of Comparative Examples 5-6 were adjusted to 1:1.37:0.6 and 1:1.37:1.1, respectively. Combined with the physical and chemical indicators of the finished product, it can be seen that the S content, particle size D50, specific surface area and Fe / P have changed significantly, and the electrical performance evaluation shows that the powder compaction density is lower than 2.45 g / cm 3 , indicating that there is a suitable range for adjusting the ratio of sulfate in the reaction solution in the fourth step, that is, the ratio of sulfate to iron ion is between 0.7 and 1.0.

[0229] Compared with Example 1, the Fe 3+ The reaction concentrations were adjusted to 0.5 mol / L and 1.1 mol / L respectively. Combined with the physical and chemical indicators of the finished product, it can be seen that the S content, particle size D50, specific surface area and Fe / P have changed significantly. After the electrical performance evaluation, the compaction density of the powder is lower than 2.45 g / cm 3 , indicating that the fifth step of adding pure water to adjust the Fe content of the reaction slurry 3+ There is a suitable range of reaction concentration, namely Fe 3+ The reaction concentration is between 0.6 mol / L and 1.0 mol / L.

[0230] Compared with Example 1, in step S3 of Comparative Example 9, the molar ratio of the aluminum removal agent added to the leachate 2 to the aluminum ions in the leachate 2 is 7.8:1. Combined with the impurity content of the finished product, it can be seen that the aluminum impurity content is 255 ppm, which exceeds the specification by 1.5 times, indicating that there is a suitable range for the maintenance ratio of the amount of the aluminum removal agent added in step 3 and the molar ratio of the aluminum ions in the leachate 2, that is, the molar amount of the aluminum removal agent: the molar amount of the aluminum ions ≥8.4:1.

[0231] Compared with Example 1, changing some of the implementation steps in Comparative Examples 10 and 11 cannot achieve the expected effects. Only by following the order of the steps in the examples can beneficial effects be achieved.

[0232] In summary, the physical and chemical indicators of the iron phosphate prepared by the process of the present invention will change with the pH of the leaching solution 1, the main component ratio of the reaction solution and the Fe content of the reaction slurry. 3+ The reaction concentration changes; the aluminum and titanium impurity content will be affected by the impurity removal conditions. Only when the pH of the leaching solution 1 is 1.6-2.4, the molar amount of the aluminum removal agent: the molar amount of aluminum ions is ≥8.4:1, and the main component ratio of the reaction solution is 1:1.15-1.40:0.7-1.0 and the reaction slurry Fe 3+ The reaction concentration is between 0.6mol / L and 1.0mol / L. The preparation conditions can stably obtain a particle size D50 of 4-6μm, an S content of 30-50ppm, and a BET of 8.5-11.5m 2 / g, Fe / P between 0.968-0.971 and aluminum and titanium impurity content <100ppm; the compacted density of the powder can reach 2.45g / cm 3 The above low-impurity and high-voltage lithium iron phosphate products.

[0233] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing ferric phosphate, characterized in that: The following steps are involved: S1 is mixed with dilute sulfuric acid, ferrophosphorus slag and iron powder, and heated and filtered to obtain carbon slag, mixed solid and leachate 1; S2 adding ammonia water to the leachate 1, filtering to obtain leachate 2; S3: adding an aluminum removal agent to the leachate 2, and filtering to obtain a leachate 3; S4 adds phosphate and sulfate to the leaching solution 3 to obtain a reaction solution; S5 adding an oxidant and water to the reaction solution to obtain a reaction slurry; S6: pouring the reaction slurry into a reaction kettle, and obtaining the iron phosphate after temperature-raising reaction, aging, washing and calcination.

2. The method according to claim 1, characterized in that: The molar ratio of the dilute sulfuric acid to the iron in the ferrophosphorus slag is 1.6-1.8:1-1.

2.

3. The method according to claim 1, characterized in that: The molar ratio of the iron powder to the iron in the ferrophosphorus slag is 0.6-0.8:1-1.

2.

4. The method according to claim 1, characterized in that: In the step S2, ammonia water is added to the leaching solution 1 to adjust the pH value of the solution to 1.6-2.

4.

5. The method according to claim 1, characterized in that: In the step S4, after the phosphate and sulfate are added to the leaching solution 3, the molar ratio of iron, phosphorus and sulfur in the leaching solution 3 is 1:1.15-1.40:0.7-1.

0.

6. The method according to claim 1, characterized in that: In step S4, the phosphate includes at least one of monoammonium phosphate, diammonium phosphate, calcium phosphate and potassium phosphate.

7. The method according to claim 1, characterized in that: In step S4, the sulfate includes at least one of ammonium sulfate, sodium sulfate, calcium sulfate, magnesium sulfate and copper sulfate.

8. The method according to claim 1, characterized in that: In step S5, the oxidant includes hydrogen peroxide.

9. The method according to claim 1, characterized in that: In step S5, Fe in the reaction slurry 3+ The concentration is 0.6-1.0mol / L.

10. A positive electrode material for a lithium battery, characterized in that: The invention comprises iron phosphate prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for recycling sulfuric acid and valuable metals in titanium dioxide waste acid

    CN115974123A

  • Preparation method of low-cost low-impurity high-compaction iron phosphate and lithium iron phosphate

    CN117509582A

  • Method for preparing battery-grade iron phosphate by recovering phosphorus iron slag after lithium extraction

    CN117602604A